The Comparison of Intrathecal Ropivacaine with Bupivacaine for Knee Arthroscopy: A Meta-analysis of Randomized Controlled Trials - Xie, Zhiwei; Nie, Xiaoying; Pan, Linlin; Zhang, Na; Xue, Huiqin (The Journal of Knee Surgery, 2020)
The comparison of intrathecal ropivacaine with bupivacaine for knee arthroscopy remains controversial. We conduct a systematic review and meta-analysis to explore the efficacy of intrathecal ropivacaine versus bupivacaine for knee arthroscopy. We search PubMed, EMbase, Web of science, EBSCO, and Cochrane library databases through August 2019 for randomized controlled trials (RCTs) assessing the effect of intrathecal ropivacaine versus bupivacaine for knee arthroscopy. This meta-analysis is performed using the random effects model. Five RCTs are included in the meta-analysis. Overall, compared with intrathecal bupivacaine for knee arthroscopy, intrathecal ropivacaine is associated with increased onset time of motor block (mean difference [MD] = 2.05, 95% CI: 1.43–2.67, p < 0.00001) and decreased duration of sensory block (MD = −26.82, 95% CI: −31.96 to −21.67, p < 0.00001) but shows no remarkable influence on onset time of sensory block (MD = −0.09; 95% CI: −1.89 to 1.70, p = 0.92), duration of motor block (MD = −59.76; 95% CI: −124.44 to 4.91, p = 0.07), time to maximum block (MD = 2.35; 95% CI: –0.16 to 4.86, p = 0.07), first urination time (MD = −26.42, 95% CI: −57.34 to 4.51, p = 0.09), or first ambulation time (MD = 3.63, 95% CI: −25.20 to 32.47, p = 0.80).Intrathecal ropivacaine can substantially increase onset time of motor block and decrease the duration of sensory block than intrathecal bupivacaine for knee arthroscopy.
Keywords: ropivacaine; bupivacaine; knee arthroscopy; randomized controlled trials; meta-analysis